The Correlation between Students' Multiple Intelligences to Students' Achievement in English Speaking Subject - Mokodompit, Andini; Mohammad, Titien Fatmawaty; Basalama, Nonny (Universitas Negeri Gorontalo, 2023)
This present study intended to examine how is the correlation between students' multiple intelligences and students' Achievement in English Speaking Subject. This research was conducted within the English language Education Study Programme at a university in the Province of Gorontalo with 50 students' year 2021 as sample which were chosen randomly. The instruments used were the Multiple Intelligence questioner, and interview, as being said this study were using both quantitative and qualitative methods. Data were analyzed by descriptive statistics the results from Pearson Correlation of students' intelligence and achievement variables. Based on the data analysis, it was found between two variables was 0.464, results showed that medium correlation existed between multiple intelligences and Students' speaking Achievement. This indicates that multiple intelligences did have affect toward students' speaking achievement. Although, seems that there was not the only factor that affects achievement. Intrapersonal, the leading intelligence type, and musical intelligence was the least common intelligence type employed by the students who participated in this research.